(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper is an attempt to analysis the correlation between literacy and sex ratio in Haryana. Literacy is one of the most important indicators of development at any region. Literacy and sex ratio is generally recognized as a major indicator of social development. As like, certain minimum level of literacy seems to be essential for a society to look out the line of poverty. Literacy affected by migration and sex ratio. The level of literacy and sex ratio is essential for the measuring the standard of living for women in society. The pace of declining sex ratio is an indicator of the neglect of girl children, sex selective abortions and traditional attributes of the society. Thus, the analysis of literacy and sex ratio is huge significant. This work found that there is positive negative correlation (r= -0.52) between literacy and sex ratio in Haryana.